KONFLIK DALAM ORGANISASI MULTIKULTURAL - Firdaus El Hadi (Jurnal Dakwah Risalah, 2013)
Modern organizations are not only dominated by one ethnic group,but a variety of ethnic groups become members of an organization. Cultural differences tends to create conflict due differences in perception. This study wanted to see how the conflict is created, and how to handle the problem with multicultural perspectives. Based on this study, conflict can be solved based on the cultural approach, because different cultures needs different approach.